2012
DOI: 10.1007/s00438-012-0709-5
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometric identification of proteins that interact through specific domains of the poly(A) binding protein

Abstract: Poly(A) binding protein (PAB1) is involved in a number of RNA metabolic functions in eukaryotic cells and correspondingly is suggested to associate with a number of proteins. We have used mass spectrometric analysis to identify 55 non-ribosomal proteins that specifically interact with PAB1 from Saccharomyces cerevisiae. Because many of these factors may associate only indirectly with PAB1 by being components of the PAB1-mRNP structure, we additionally conducted mass spectrometric analyses on seven metabolicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(44 citation statements)
references
References 75 publications
2
41
1
Order By: Relevance
“…We further showed that four RRM domains in Pab1 (RRM1-4) are required for the binding with Sbp1. Consistent with our results, Sbp1 was identified to associate with Pab1 in a recent study (Richardson et al 2012). Pab1 and eIF4G were known to interact with each other (Tarun and Sachs 1996;Tarun et al 1997;Kessler and Sachs 1998).…”
Section: Sbp1 Binds To the Poly(a) Region In 5 ′ ′ ′ ′ ′ Utr Pab1 Spesupporting
confidence: 93%
“…We further showed that four RRM domains in Pab1 (RRM1-4) are required for the binding with Sbp1. Consistent with our results, Sbp1 was identified to associate with Pab1 in a recent study (Richardson et al 2012). Pab1 and eIF4G were known to interact with each other (Tarun and Sachs 1996;Tarun et al 1997;Kessler and Sachs 1998).…”
Section: Sbp1 Binds To the Poly(a) Region In 5 ′ ′ ′ ′ ′ Utr Pab1 Spesupporting
confidence: 93%
“…By 6 min the mRNA was already present in two distinct bands (long poly(A) tails with average length 60 A’s and a short poly(A) pool with average length about 13 A’s as determined by densitometric analysis, not shown). The presence of two bands is characteristic of rapid processive deadenylation in which long poly(A) tails co-exist with short poly(A) tail lengths (Decker and Parker 1993; Olivas and Parker 2001; Viswanathan et al 2003, 2004; Lee et al 2010; Richardson et al 2012). These results were supported by the observation that GAL1-S deadenylation was also noticeably faster in the PAB1-T102D P103V background.…”
Section: Resultsmentioning
confidence: 99%
“…Because the RRM1 domain of PAB1 makes contacts to eIF4G that is involved in forming translational complexes (Richardson et al 2012), it is possible that PAB1-T102D P103V is accelerating deadenylation by disrupting the formation of translating ribosomes. We have shown in other research that the cdc33-1 allele reduces by two-fold the ability of the 77S monosomal translation complex to be formed (Figure 6B) (Wang et al 2012).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, mutations at residues 180-181 (KE) and 184-186 (DAL), which are part of the eIF4G binding site in helix α2 (Otero et al 1999), had only minor effects on cell growth (median enrichment score 0.89). In vitro, mutations at these sites result in complete loss of eIF4G binding and diminished mRNA translation (Otero et al 1999), but in vivo, a weak affinity of RRM1 for eIF4G may compensate for loss of eIF4G binding by RRM2 (Kessler and Sachs 1998;Richardson et al 2012). Lastly, of the loop regions, L2, which connects helix α1 to strand β2 by a four amino acid turn, was the least resistant to mutation (median enrichment score 0.19), making it the most sensitive element after strands β1 and β3.…”
Section: Effect Of Single Amino Acid Substitutionsmentioning
confidence: 99%
“…The RRM domains associate directly with the RNA molecule, while the C-terminal region is not required for RNA binding or yeast viability (Sachs et al 1987;Burd et al 1991). In addition to poly(A) binding, all Pab1 RRM domains mediate protein-protein interactions (Kessler and Sachs 1998;Yao et al 2007;Richardson et al 2012). In particular, binding of Pab1 RRM2 to the eukaryotic initiation factor 4G (eIF4G) (Kessler and Sachs 1998) is presumed to promote the formation of a closed-loop structure between the mRNA cap and the poly(A) tail (Jacobson and Favreau 1983;Wells et al 1998;Amrani et al 2008) and to stimulate mRNA translation (Tarun et al 1997;Imataka et al 1998;Park et al 2010).…”
Section: Introductionmentioning
confidence: 99%